Community Health Workers’ Digital Competencies in Using Digital Technologies and Artificial Intelligence - Sabrina Intan Zoraya; Abdillah Adipatria Budi Azhar; Winda Kurnia Sari; Iman Saladin Budi Azhar; Rizma Adlia Syakurah (Al-Hijrah Indonesia, 2026)
Background: Strengthening community health workers’ (CHWs) digital competencies is critical to ensuring that digital health transformation translates into improved community-level services. Aims: This systematic review aimed to synthesize evidence on the effectiveness of training, empowerment, or capacity-building interventions in enhancing CHWs’ competencies in using digital technologies and artificial intelligence (AI). Methods: Following PRISMA guidelines, articles published between 2016 and 2026 were identified from four databases. Quantitative studies and community-based implementation reports assessing improvements in digital knowledge and/or skills were included. Results: Of 885 records screened, 30 met eligibility criteria. Interventions encompassed mobile health applications, web-based information systems, digital data management tools, and AI-assisted screening platforms. Most studies reported significant gains in knowledge scores, digital data entry and reporting skills, electronic form management, digital surveillance, and AI-assisted interpretation. Improvements in data completeness, timeliness, and perceived reporting accuracy were also documented. However, sustainability challenges emerged, including limited internet infrastructure, unequal access to devices, heterogeneous baseline digital literacy, reliance on external mentoring, short-term evaluations, and incomplete integration with routine health information systems. Conclusion: Overall, structured digital training interventions consistently enhance CHWs’ competencies and support the strengthening of primary health care. Sustainable impact, however, requires institutional embedding, standardized tiered training, infrastructure investment, and governance mechanisms to prevent digital initiatives from remaining fragmented pilot projects.